LC–MS/MS simultaneous analysis of allopregnanolone, epiallopregnanolone, pregnanolone, dehydroepiandrosterone and dehydroepiandrosterone 3-sulfate in human plasma. (March 2017) - Lionetto, Luana; De Andrés, Fernando; Capi, Matilde; Curto, Martina; Sabato, Donata; Simmaco, Maurizio; Bossù, Paola; Sacchinelli, Eleonora; Orfei, Maria Donata; Piras, Federica; Banaj, Nerisa; Spalletta, Gianfranco
Aim: Several neuropsychopharmacological properties have been attributed to the 3α-reduced pregnane steroids, allopregnanolone and pregnanolone, as well as to dehydroepiandrosterone sulfate because of their ability to modulate γ-aminobutyric acid (GABAA ) receptors in the CNS. In order to understand better their role in several mechanisms in CNS, a new methodology is proposed to monitor these compounds in human plasma.Methodology & results: The analytes were first derivatized with 2-hydrazinopyridine and extracted from plasma using SPE. Then, the compounds were separated and detected by LC–MS/MS. A mobile phase of formic acid (0.1%) in water and methanol through a gradient of composition and a flow rate of 0.3 ml min -1 resulted in good separations of the analytes. Linear responses in wide range of concentrations and LOQs ranging from 10 (dehydroepiandrosterone 3-sulfate) to 40 pg ml -1 (dehydroepiandrosterone) were obtained in <9 min. The method proposed has been validated and then applied to monitor these neurosteroids in plasma samples from ten volunteers.Conclusion: For the first time, a straightforward and reliable method for the chromatographic separation of allopregnanolone, epiallopregnanolone and pregnanolone, as well as of dehydroepiandrosterone and dehydroepiandrosterone 3-sulfate was carried out, with optimal accuracy, sensitivity and specificity.